Commercial opportunities of products from oriente antioqueño in the chinese market - Ceballos Ramírez, Silvia Liliana; Lukau Quintero, Claudia Elena; Duque Castaño, Yeny Paola (Universidad Francisco de Paula Santander, 2024)
This research aims to identify commercial opportunities for products from the Oriente Antioqueño in the Chinese market, providing timely information to exporting companies in the region. This study follows a quantitative research approach, as it is approached through the quantification and analysis of numerical and statistical data, allowing for the collection of data on the 19 products demanded by the Chinese market and offered by companies located in oriente Antioqueño. As a result, the identification of 19 products with export potential for the Chinese market was obtained. These products include: belts, socks, freeze-dried instant coffee, underwear, confections, gold, foliage, caps, handbags, swimwear, wood, fruit pulps, mineral water, ice skates, sand, pigments, trout, Hass avocados, and polypropylene. The products from Oriente de Antioquia identified in this article with export potential for the Chinese market highlight the need for markets to exchange products. Therefore, it is important to understand the dynamics of trade, the signing of free trade agreements, and the challenges of globalization so that coherent strategies can be formulated to enter these markets and succeed in the internationalization process.